A new portable vibrator for plaster pouring: effect on the marginal fit at cylinder-abutment (Journal of Applied Oral Science, 2012)
OBJECTIVE: The aim of this study was to test a new portable vibrator for plaster pouring (developed for this purpose), comparing the effect of its use on the accuracy of working cast of implant-supported restorations to the conventional vibrator. MATERIAL AND METHODS: From a master cast with 2 implants, 30 transfer moldings were made randomly and divided into three groups: Group I (GI): pouring performed in an outsourced dental laboratory with conventional plaster vibrator (10 casts), Group II (GII): pouring performed in the laboratory of the Federal University of Santa Catarina (UFSC) with conventional plaster vibrator (10 casts) and Group III (GIII): pouring performed with the portable vibrator fabricated for this study (10 casts). The position of the analogue and marginal adaptation of the infrastructure were verified by testing the single screw on the master model and on the working model. The measurement of misfit was blindly performed with a precision microscope and analyzing unit, Quadra-Check 200. The data were statistically analyzed by analysis of variance (ANOVA) and the Holm-Sidak test (α=0.05). RESULTS: Means±standard deviations were as follows: GI: 19.19±4.73 µm; GII: 21.72±5.41 µm; GIII: 13.5±2.39 µm (P